2019
DOI: 10.3390/genes10090694
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Expression, and Interaction Analyses of OsMORF Gene Family in Rice

Abstract: The multiple organellar RNA editing factors (MORF) gene family plays a key role in organelle RNA editing in flowering plants. MORF genes expressions are also affected by abiotic stress. Although seven OsMORF genes have been identified in rice, few reports have been published on their expression patterns in different tissues and under abiotic stress, and OsMORF–OsMORF interactions. In this study, we analyzed the gene structure of OsMORF family genes. The MORF family members were divided into six subgroups in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…MORFs are a small protein family in land plants. Members of the MORF gene family have been widely identified in genomes of several species, such as A. thaliana with nine members, P. trichocarpa with nine [7], O. sativa with seven [17], Z. mays with seven [18], and Nicotiana with nine [19]. MORF proteins harbor a conserved stretch of residues (MORFbox), and form homo-and heteromers to interact with selected PPR proteins; however, the molecular function of the MORF-box remains elusive because it shares no sequence similarity with known domains [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MORFs are a small protein family in land plants. Members of the MORF gene family have been widely identified in genomes of several species, such as A. thaliana with nine members, P. trichocarpa with nine [7], O. sativa with seven [17], Z. mays with seven [18], and Nicotiana with nine [19]. MORF proteins harbor a conserved stretch of residues (MORFbox), and form homo-and heteromers to interact with selected PPR proteins; however, the molecular function of the MORF-box remains elusive because it shares no sequence similarity with known domains [20].…”
Section: Introductionmentioning
confidence: 99%
“…MORF2 and MORF9 can directly physically interact to form complexes that affect the RNA editing of NADH dehydrogenase subunit 4 (ndhD) in chloroplasts, whereas MORF8 can interact with MORF1 and MORF2 in mitochondria and chloroplasts, respectively [22,23]. Expressions of six and seven MORF genes in O. sativa were proved to be affected by cold and salt stresses, respectively [17]. In poplar, it has been reported that the PtrMORF genes responded to drought [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a post-transcriptional modification process, RNA editing fine-tunes gene expression and functions by altering specific nucleotides of a transcript ( Oldenkott et al, 2020 ). In flowering plants, RNA editing generally changes cytidine to uridine in plastids and mitochondria, playing important roles in organelle biogenesis, adaptation to environmental changes, and signal transduction; PPR, MORF, and ORRM proteins play curial roles in plant RNA editing ( Lu, 2018 ; Zhang et al, 2019 ; Small et al, 2020 ). Here, we found that the mutation of PLS-PPR protein, GmPGL2, caused the abnormal chloroplast development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PPR proteins are essential for the normal activities of the mitochondria and chloroplasts as the majority of the PPR protein mutants display varied physiological phenotypes, such as pigment deficiency ( Pyo et al, 2013 ; Huang et al, 2018 ), photosynthetic defects ( Cai et al, 2009 ; Johnson et al, 2010 ), seedling lethality ( Sun et al, 2018 ; Li et al, 2019 ), and restricted growth ( Sung et al, 2010 ; Hu et al, 2012 ; Xiao et al, 2018 ). Recent studies have shown that MORF2, MORF8, and MORF9 are localized to plastids and are required for chloroplast RNA editing ( Yan et al, 2017 ; Huang et al, 2019 ; Zhang et al, 2019 ; Zhao et al, 2019 ); ORRM1 and ORRM6 are also localized to plastids and participate in chloroplast RNA editing ( Searing et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…First-strand cDNA was obtained using a ReverTra Ace qPCR RT Kit (TOYOBO). The quantitative real-time PCR (qRT-PCR) experimental procedure was as described in a previous study [27]. In the present study, the OsAction1 gene was used as an internal control, and the relative expression levels of genes were calculated using the 2 −∆∆CT method [28].…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%